SISTEM INFORMASI PROMOSI DAN PEMESANAN STUDIO FOTO DEMAHOUSE BERBASIS WEB DI KOTA JAMBI: Database, Foto, Online, Studio, Website - Indriani, Tia; Rahmawati, Noni; Kurniawan, Tomi (JURNAL AKADEMIKA, 2025)
The web-based promotion and ordering information system is designed to facilitate users in ordering photography packages online. This website makes it easy for users to find information about Demahouse Studio and conduct promotions, simply through the website. This system also simplifies data management for administrators, including package data, order data, gallery data, and transaction data. Prior to this website, Demahouse Studio still used manual ordering and data management, resulting in no valid order data storage. Users seeking photography services had to book directly with the studio. By utilizing information technology, the website is expected to simplify user access and compete with other studios. To facilitate this, attractive and up-to-date promotional media and information are also needed on the website.